2017
DOI: 10.3390/su9101869
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Energy Efficiency Measures and Retrofitting Solutions for Social Housing Buildings in Spain as a Way to Mitigate Energy Poverty

Abstract: Energy poverty is a common issue in social housing all over Europe, with a harder impact in Southern European countries. Social housing buildings play an important role in energy poverty. They are usually owned and managed by public institutions and usually share common characteristics and issues. Behavioural changes and energy retrofitting are interesting paths forward but some solutions do not fit well in this type of housing due to socioeconomic reasons. This paper makes a thorough analysis of possible ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 38 publications
(42 reference statements)
0
17
0
1
Order By: Relevance
“…An analysis of energy efficiency measures and retrofitting solutions for social housing buildings in Spain as a way to mitigate energy poverty was recently published by Aranda et al Indeed, they reported that energy simulation tools have proven to be affordable, fast, and convenient for assessing the energy-saving potential of each measure implemented in a building. However, the real savings values are usually 20-30% lower than the simulated results, mainly because simulated demand is calculated to meet standard thermal comfort conditions, which are not always met in this type of housing due to its economic limitations [29]. Another paper dealing with an early-1950s building presents a measurement campaign to investigate the building's characteristics and its vulnerability.…”
Section: Building Retrofittingmentioning
confidence: 99%
“…An analysis of energy efficiency measures and retrofitting solutions for social housing buildings in Spain as a way to mitigate energy poverty was recently published by Aranda et al Indeed, they reported that energy simulation tools have proven to be affordable, fast, and convenient for assessing the energy-saving potential of each measure implemented in a building. However, the real savings values are usually 20-30% lower than the simulated results, mainly because simulated demand is calculated to meet standard thermal comfort conditions, which are not always met in this type of housing due to its economic limitations [29]. Another paper dealing with an early-1950s building presents a measurement campaign to investigate the building's characteristics and its vulnerability.…”
Section: Building Retrofittingmentioning
confidence: 99%
“…Investments may consider building-envelope retrofitting and heating-equipment replacement, but only the former translate into energy-poverty alleviation and indoor-comfort improvements [61]. These investments should be undertaken by the public entity that owns the dwellings [31], and the improvements should be included in a holistic programme of refurbishing and improving social housing, as noted by Swan et al [62]. …”
Section: Energy Poverty: An Empirical Analysismentioning
confidence: 99%
“…Often, researchers argue that deep retrofitting solutions are costly and they usually need a temporary relocation of tenants. However, as in Aranda et al [69], some solutions are proposed, such as working on the building envelopes, on lighting systems and on energy generation. Nevertheless, less disruptive and low-cost retrofitting solutions (also not linked to solving energy poverty) have been studied by architectural and engineering researchers for years, but they do not seem to constitute the unique response to fuel poverty because, as many authors argue, fuel and energy poverty also involves social, political, and economic concerns [70][71][72][73][74].…”
Section: Mitigation Strategies From Literaturementioning
confidence: 99%